Risk factors that limit use of oral JAK inhibitors in chronic hand eczema: Findings from the Danish Skin CohortCapsule Summary - Yuki M.F. Andersen, MD, PhD; Johan Sieborg, MSc; Lea Nymand, MSc; Tiago Torres, MD, PhD; Andrea Chiricozzi, MD; Simon Francis Thomsen, MD, PhD, DMSc; Jacob P. Thyssen, MD, PhD, DMSc; Alexander Egeberg, MD, PhD, DMSc (Elsevier, 2024)
Background: Oral Janus kinase inhibitors (JAKis) have black-box warnings of infections, cancer risk, and cardiovascular and venous thromboembolic events. They may be used off-label for chronic hand eczema (CHE). Objectives: Assess the prevalence of risk factors potentially impacting oral JAKi safety in CHE patients. Methods: In the Danish Skin Cohort, CHE patients were examined for risk factors affecting oral JAKi use at baseline and followed for 12 months. Data were collected through register linkage (eg, cancer history) and through patient interviews (eg, smoking habits). Results: Of 941 adults with CHE (66.2% women; mean age 55.5 [SD 13.3] years), 768 (81.6%) patients had at least one risk factor potentially impacting oral JAKi use, of which 682 (72.5%) had nonmodifiable risk factors. Most common risk factors were current or former heavy smoking (62.8%, n = 591), obesity (28.1%, n = 264), hypercholesterolemia (21.5%, n = 202), and hypertension (18.8%, n = 177). Among patients without any risk factors at baseline (n = 173), 20.2% (n = 35) developed ≥1 risk factor during the following 12 months. Limitations: Certain risk factors may be underreported. Conclusion: Most CHE patients have risk factors limiting appropriateness of oral JAKi use. Health care providers should assess risk factors in their patients when choosing treatment for CHE.